Stresses and Strains Induced in a Building Wall by Slow Harmonic Thermo-Humiditive Diffusion - Dudziak, W.; Uklejewski, R. (Engineering Transactions, 1992)
The Podstrigač-Nowacki theory of thermodiffusion in deformable solids has been used to describe the coupled processes of heat and moisture transport through building walls. The analytic solutions for the stresses and strains induced in a wall material by slow harmonic thermo-humiditive diffusion process are obtained by means of the electric transmission line theory, owing to the electro-elasto-thermo-diffusive analogies.